ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN CERITA PENDEK PADA FASE C SEKOLAH DASAR - Endang Nofriani; Eko Kuntarto; Andi Gusmaulia Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze students' reading comprehension skills in phase C of elementary school, especially in understanding short stories. The main focus of this study is to identify and evaluate students' abilities in three main aspects: determining the main idea, answering questions comprehensively, and retelling the content of the reading. The research was conducted at SDN 95/VI Parit Ujung Tanjung I in June 2024. This research used a qualitative approach with a case study research type. The data in this study were obtained directly through observation, reading comprehension tests given to students and interviews to get an in-depth picture of students' ability to understand short stories. The subjects in this study were grade V students. The data validity test used triangulation of techniques and time. The results of this study showed that: (1) 2 out of 12 students have been able to determine the main idea with a percentage of 14.5% while the rest still have difficulty in determining the main idea. The difficulties faced by students in determining the main idea are caused by limitations in vocabulary which hinder their understanding (2) Students' ability to answer questions comprehensively shows that 4 out of 12 students have been able to answer questions with a percentage of 22% while the rest still have difficulties. These difficulties are caused by students not understanding the questions well. In addition, students also tend to rush and be less careful in solving problems (3) Students' ability to retell the content of reading shows that 3 out of 12 students have been able to retell the content of reading well. However, the rest still have difficulties. The difficulties experienced by students include difficulty remembering the details of the story, not being able to retell the content of the reading with their own version as seen from the answers of students who only copy the reading text. From this study it can be concluded that the ability to read comprehension of short stories in phase C of elementary school is still in the deficient category.